2001
DOI: 10.1136/jnnp.70.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal peripheral auditory asymmetry in schizophrenia

Abstract: Objective-Auditory processing diYculties have been reported in schizophrenia. This study explores peripheral auditory function in patients with schizophrenia in whom certain early disturbances of auditory message filtering have been found and may be associated with certain abnormalities which are particularly localised in the left temporal lobe. Methods-Otoacoustic emissions, including click evoked and spontaneous emissions and measurements of functioning of the medial olivocochlear eVerent system were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 62 publications
(42 reference statements)
0
23
2
5
Order By: Relevance
“…Significant right-ear advantage of MOCS functioning, reported in the literature for some normalhearing adult populations (Khalfa & Collet, 1996;Veuillet et al, 2001) was not replicated here in either the control or the SLI group. It has been hypothesized that asymmetry of MOCS activity may be linked with more central asymmetry.…”
Section: Teoae Contralateral Suppression/ Mocs Functioningcontrasting
confidence: 77%
“…Significant right-ear advantage of MOCS functioning, reported in the literature for some normalhearing adult populations (Khalfa & Collet, 1996;Veuillet et al, 2001) was not replicated here in either the control or the SLI group. It has been hypothesized that asymmetry of MOCS activity may be linked with more central asymmetry.…”
Section: Teoae Contralateral Suppression/ Mocs Functioningcontrasting
confidence: 77%
“…A greater contralateral suppression of EOAEs was found in musicians compared to nonmusicians Perrot et al, 1999) and reduced suppression has been reported in children with auditory processing disorders Sanches and Carvallo, 2006) and selective mutism (Bar-Haim et al, 2004). Moreover, most population studies have found a greater suppression in right than left ears (Khalfa and Collet, 1996;Khalfa et al, 1998), which has been suggested to be linked to the hemispheric asymmetry in sound processing (Morand-Villeneuve et al, 2005;Philibert et al, 1998), which may be altered in autism and schizophrenia (Khalfa et al, 2001a;Veuillet et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
“…Among the different sensory modalities, the auditory modality is of particular interest for schizophrenia [Veuillet et al, 2001], because schizophrenia particularly affects auditory processing [Bentaleb et al, 2002]. While processing deficits of the visual domain are typically evoked by structural brain damages [Prigatano and Wong, 1999], auditory verbal hallucinations are one of the most characteristic symptoms of schizophrenia [David, 1999].…”
Section: The Auditory Stroop Approach For Clinical Purposesmentioning
confidence: 99%
“…Abnormal conflict management was evidenced for several brain disorders, e.g., attention-deficit/hyperactivity disorder [for review see Lansbergen et al, 2007] or in paranoid schizophrenia [Nordahl et al, 2001]. An auditory approach to the common Stroop interference task seems of particular interest since the auditory sense is especially affected in psychiatric disorders such as schizophrenia [Veuillet et al, 2001]. Recently, it has been reported that an increased Stroop effect can serve as a marker for a genetic vulnerability to schizophrenia [e.g., Becker et al, 2008;Filbey et al, 2008].…”
Section: Introductionmentioning
confidence: 99%